The Mediating Effect of Affective Commitment in The Influence of Job Satisfaction on Organizational Citizenship Behavior - Laumeka, Hanifah; Fitria, Yuki (Human Resource Management Studies, 2024)
This research aims to determine and analyze the impact of job satisfaction on organizational citizenship behavior through affective commitment in employees of the Payakumbuh City Transportation Department. This type of research is descriptive causative research. The respondents of this study were 42 people using total sampling techniques. Data collection using a questionnaire with a Likert scale. Data analysis techniques using SEM with the help of SmartPLS software version 4.0.1. The research findings show that job satisfaction has a positive and significant impact on organizational citizenship behavior. Job satisfaction has a positive and significant impact on affective commitment. In addition, this study also proves that affective commitment mediates the impact of job satisfaction on organizational citizenship behavior positively and significantly.